Islamic Education Teacher's Strategy in Building Resilience in Students with Broken Home Family Backgrounds - Amalia, Neneng; Arifin, Mohamad Zaenal; Samsudin, Umar; Ghofur, Abdul (Al-Hayat: Journal of Islamic Education, 2025)
Students from broken home family backgrounds are prone to mental and behavioural disorders, such as anxiety, sadness, stress, feeling unloved and unloved, lack of self- confidence, difficulty controlling emotions, and being violent to friends. This affects not only students' psychological and social conflicts but also the quality of their learning at school. This study aims to describe the efforts made by Islamic Education teachers to help students with broken home family backgrounds deal with the problems that occur. This research is qualitative research with a case study approach. The research subjects were four Islamic Education teachers, two homeroom teachers, and five students with broken home family backgrounds. Data collection techniques were carried out by observation and interviews. Data analysis techniques were reduction, display, verification, and conclusion drawing. This study found that the problems faced by students with broken home family backgrounds are parents being too busy, communication breakdowns in the family, egocentric attitudes of parents, low family economic levels, and infidelity. Islamic Education teachers can overcome the negative impacts arising from the problems of broken home families by building resilience in students by instilling emotion regulation, self-control, optimism, empathy, and self efficacy. This study has limitations because it only uses descriptive analysis of limited data. Therefore, it is hoped that there will be further studies with more data coverage, such as the involvement of Counselling Guidance teachers and students' parents.